Romania's tobacco excise policy in 2025: Missed opportunity ahead of the EU Tobacco Taxation Directive update - Nora Kungl; Hana Ross; George Stefan (The Vienna Institute for International Economic Studies (wiiw), 2025)
In August 2025, as part of a large fiscal package, Romania announced an increase in tobacco and alcohol excise taxes, news welcomed by proponents of public health. However, the announcement turned into a disappointment for the tobacco control community when the final increase in cigarette excise tax amounted to only 2.25%. This policy note outlines the reform and uses a simulation model to demonstrate the missed opportunity to adopt pro-health tobacco tax policy. By not implementing a 10% increase, as for other excises, the newly adopted schedule not only fails to reduce smoking prevalence but also deprives Romania of an opportunity to collect RON 1.657bn (EUR 326.6m) in additional tax revenues in 2025-2027. Moreover, an accelerated tax roadmap aligning Romania with the proposed EU Tobacco Taxation Directive by 2027 would raise an additional RON 4.73bn (EUR 932m), reduce smoking prevalence by 4%, and avert nearly 50,000 smoking-related premature deaths.
Keywords: H24; I18; 330; Excise; Taxation; Tobacco; Smoking